El límite imposible de un republicano cordobés, Antonio Jaén Morente (1879-1964) - Masaya Watanabe (Cahiers de Civilisation Espagnole Contemporaine)
Brief portrait of the historian and Republican Congressman Cordovan Antonio Jaén Morente, that the victory of Franco in 1939 forced, like many others, to take the path of exile.